2013
DOI: 10.1021/ja406016j
|View full text |Cite
|
Sign up to set email alerts
|

A New High-Energy Cathode for a Na-Ion Battery with Ultrahigh Stability

Abstract: Large-scale electric energy storage is a key enabler for the use of renewable energy. Recently, the room-temperature Na-ion battery has been rehighlighted as an alternative low-cost technology for this application. However, significant challenges such as energy density and long-term stability must be addressed. Herein, we introduce a novel cathode material, Na1.5VPO4.8F0.7, for Na-ion batteries. This new material provides an energy density of ~600 Wh kg(-1), the highest value among cathodes, originating from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
291
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(314 citation statements)
references
References 58 publications
15
291
1
4
Order By: Relevance
“…expand or shrink only o3% throughout the range of electrochemical cycling (Supplementary Table 1), which reflects the stable crystal structure of open-framework PBAs 12,33 . The overall volume expansion is 1.36%, which is the lowest value ever observed for NIBs 10 .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…expand or shrink only o3% throughout the range of electrochemical cycling (Supplementary Table 1), which reflects the stable crystal structure of open-framework PBAs 12,33 . The overall volume expansion is 1.36%, which is the lowest value ever observed for NIBs 10 .…”
Section: Resultsmentioning
confidence: 63%
“…In the past, researchers have explored the possibility of adapting positive electrode materials of LIBs, including Na super ionic conductor structures 7 , layered oxides 5,8 , tunnel-structured oxides 9 and fluorophosphates 10 , for Na þ intercalation. However, close-packed, oxide-ion arrays connected by first-row transition metal elements do not have enough interstitial space in the structure for rapid Na þ diffusion 11 .…”
mentioning
confidence: 99%
“…b) Energy density of Na 1.5 VPO 4.8 F 0.7 compared with various cathode materials for NIBs and Li‐ion batteries. Reproduced with permission 94. Copyright 2013, American Chemical Society.…”
Section: Recent Advances In Polyanion‐type Electrode Materials For Namentioning
confidence: 99%
“…The reaction mechanisms during charge/discharge process include combinations of solid solution and two‐phase reaction behavior, but the structural motif was maintained throughout these reactions 223. The relationship among V 3+ /V 4+ /V 5+ redox reactions, Na + −Na + ordering, and Na + intercalation mechanisms of Na 3 (VO 1− x PO 4 ) 2 F 1+2 x in SIBs were investigated by Park et al through a combined theoretical and experimental approach 218, 224. They found that the redox mechanism and phase reactions varied with fluorine content.…”
Section: Mixed‐anion Materials For Na Storagementioning
confidence: 99%